Food Pathways of Salmonella and Its Ability to Cause Gastroenteritis in North Africa - Mohamed-Yousif Ibrahim Mohamed; Hazim O. Khalifa; Ihab Habib (Foods)
Infections caused by human pathogenic bacteria in food sources pose significant and widespread concerns, leading to substantial economic losses and adverse impacts on public health. This review seeks to shed light on the recent literature addressing the prevalence of Salmonella in the food supply chains of North African countries. Additionally, it aims to provide an overview of the available information regarding health-related concerns, such as virulence genes, and the presence of antibiotic resistance in Salmonella. This review highlights a gap in our comprehensive understanding of Salmonella prevalence in the food supply chains of North African nations, with limited molecular characterization efforts to identify its sources. Studies at the molecular level across the region have shown the diversity of Salmonella strains and their virulence profiles, thus, these results show the difficulty of controlling Salmonella infections in the region. In addition, the discussion of antibiotic resistance makes it clear that there is a need for the development of comprehensive strategies to fight the potential threat of antimicrobial resistance in Salmonella strains. Despite common reports on animal-derived foods in this region, this review underscores the persistent challenges that Salmonella may pose to food safety and public health in North African countries.